The Influence Of The Tahfidzul Qur’an Program On The Character Forming Of The Nurul Huda Islamic Boarding School - Nawawi, Ahmad (Prosiding University Research Colloquium, 2021)
The decline in character has become a common sight that is clearly seen in the daily lives of teenagers. Therefore, it is necessary to carry out various efforts from educational institutions to return humans to goodness, as well as prevent the growth and development of negative characters in students, as early as possible. One program that is able to shape the character of students is the Tahfidzul Qur'an program. With the program to memorize the Qur'an, students will know better what to do and what to leave behind. This study aims to prove the influence of the Tahfidzul Qu'ran program on the character formation of the students of the Nurul Huda Islamic Boarding School Purbalingga. Samples were taken as many as 100 students of the Islamic Boarding School Nurul Huda Purbalingga. The data analysis technique used is simple linear regression. The results showed that the tahfidzul qu'ran program had an effect on the formation of the character of students. Tahfidz Al-Qur'an education at the Islamic Boarding School Nurul Huda Purbalingga serves as an introduction, habituation, and inculcation of noble character values to students in order to build people of faith and piety to Allah SWT. A person's character is formed through habits that are carried out. If good habits are carried out by someone, a good character will be formed, as well as if what is accustomed is bad things, it will form a character that is not in a person. The formation of the character of students is very important and should not be ignored by anyone for the future of the nation and the maintenance of religion. The formation of the character of students is the responsibility of every person, family, school, community, and government.